Public awareness about in vitro fertilisation in the Republic of Belarus - Salmina, Anastasiya V. (Journal of the Belarusian State University. Sociology, 2023)
Through a sociological survey, the awareness of Belarusian residents about the problem of the prevalence of infertility and the use of in vitro fertilisation is assessed. The representative republican sample consisted of 1805 respondents. An analysis of the results indicates a high level of respondents’ awareness of the prevalence of infertility and the regulation of the use of assisted reproductive technologies. However, a third of the population believes that the problem of infertility and methods of its treatment are not covered in full. The main provider of information about new types of in vitro fertilisation for respondents is healthcare organisations. Almost every second person thinks that there is no financial support for infertile couples in Belarus. This fact indicates insufficient awareness of the population about the in vitro fertilisation procedure in the Republic of Belarus at the expense of the state budget and may become an economic barrier to its use.
Keywords: assisted reproductive technologies; in vitro fertilisation; public awareness; demographic policy; sociological research